2009
DOI: 10.1111/j.1467-9655.2009.01580.x
|View full text |Cite
|
Sign up to set email alerts
|

Ashéninka amity: a study of social relations in an Amazonian society

Abstract: Starting with Ashéninka people's avowed preference for living apart, in nuclear family households, this article analyses Ashéninka social practices within the context of ongoing academic debates over reciprocity, kinship, and the relative importance of similarity and difference in Amazonian thought. I argue that instead of attempting to pull others into fixed and narrowly prescribed relationships, particularly those based on kinship, the Ashéninka prefer for all ties to be based on relations of friendship that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…As various authors have observed, it tends to involve unrelated persons (that is, lacking consanguineal or affinal ties) who often come from spatially and socially distant residential units (Brightman ; Howard ; Rivière ; Van Velthem ). It thus follows the pattern emphasized by Santos‐Granero () and Killick (), according to which trading partnerships in native Amazonia represent forms of relationality that bypass the quotidian conventions required from the process of kinship‐making.…”
supporting
confidence: 52%
“…As various authors have observed, it tends to involve unrelated persons (that is, lacking consanguineal or affinal ties) who often come from spatially and socially distant residential units (Brightman ; Howard ; Rivière ; Van Velthem ). It thus follows the pattern emphasized by Santos‐Granero () and Killick (), according to which trading partnerships in native Amazonia represent forms of relationality that bypass the quotidian conventions required from the process of kinship‐making.…”
supporting
confidence: 52%
“…Their system of delayed reciprocity (Killick 2008) serves to maintain dayto-day commercial relationships as well as providing access started secondary school but not completed, = 5 completed secondary school, = 6 started superior school but not completed, = 7 completed superior school b Agricultural income refers to last 12 months, non-agricultural income to last 6 months (approximately 1 Nuevos Soles = USD 3) c The farmers' seed lot is not located by river (refers to the largest seed lot: only one farmer had seed lots located both by and off river) to unrelated brides for young men. The system encompasses village households and also outsiders, such as mestizos, who also base some of their economic transactions on reciprocity (Killick 2008(Killick , 2009). The main collective action institution in the study area is locally (and in other parts of Peru such as the Altiplano) known as minga.…”
Section: The Case Studymentioning
confidence: 99%
“…Responses to Viveiros de Castro's characterization, from the perspective of moral economy, can be found in McCallum () and Overing and Passes (2000 a ). Some more recent discussions have sought to push the debate forward by exploring friendship as a kind of ‘middle ground’ between consanguinity and affinity, or between conviviality and predation (see Fausto ; Killick ; Santos‐Granero )…”
Section: Trade and Theories Of Exchangementioning
confidence: 99%